The Paeonia qiui R2R3-MYB Transcription Factor PqMYB113 Positively Regulates Anthocyanin Accumulation in Arabidopsis thaliana and Tobacco - Liu, Xiaokun; Duan, Jingjing; Huo, Dan; Li, Qinqin; Wang, Qiaoyun; Zhang, Yanlong; Niu, Lixin; Luo, Jianrang (Frontiers in Plant Science, 2022)
Paeonia qiui is a wild species of tree peony native to China. Its leaves are purplish red from the bud germination to the flowering stage, and anthocyanin is the main pigment in purplish red leaves. However, the anthocyanin synthesis regulation mechanism in tree peony leaves remains unclear. In this study, an R2R3-MYB, PqMYB113 was identified from the leaves of P.qiui. Phylogenetic analysis revealed that PqMYB113 clustered with Liquidambar LfMYB113 and grape VvMYBA6. Subcellular location analysis showed that PqMYB113 was located in the cell nucleus. The transient reporter assay suggested that PqMYB113 was a transcriptional activator. The overexpression of PqMYB113 in Arabidopsis thaliana and tobacco (Nicotiana tabacum) resulted in increased anthocyanin accumulation and the upregulation of CHS, F3H, F3’H, DFR, ANS. The dual luciferase reporter assay showed that PqMYB113 could activate the promoters of PqDFR and PqANS. Bimolecular fluorescence complementation assays and yeast two-hybrid assays suggested that PqMYB113 could form a ternary MBW complex with PqbHLH1 and PqWD40 cofactors. These results provide insight into the regulation of anthocyanin biosynthesis in tree peony leaves.